Robust electron-correlation and colossal magnetoresistance of complex composition Co0.5Mg0.5AlxFe2–xO4 with x = 0.0, 0.25, 0.5, 0.75, and 1.0. (1st July 2022) - Soliman, S; Zaki, H M; Solyman, S
Abstract : For antisymmetric cobalt magnesium ferrite alloys, Co0.5 Mg0.5 Al x Fe2− x O4 ab-initio calculations were used to study the strain and Al-doping contributions to the rearrangement of magnetic structure ordering state, where x = 0.0, 0.25, 0.5, 0.75, and 1.0. According to the calculations, the ground state without the Hubbard parameter is half-metallic with an antiferromagnetic structure. A side magnetic transition from antiferromagnetic to ferromagnetic is established due to crystal magnetic symmetry aberrations caused by strain and Al-doping. The magnetic phase transition happens even at low pressure levels, such as 0.4 GP for Co0.5 Mg0.5 Al0.25 Fe1.75 O4 . According to the calculated data, A-side and B-side oxygen have different activities. The Fermi level nesting grows with pressure in the majority channel and becomes defined in shape, predicting a decrease in resistance. The Fe-3d electron-correlation is shown to have a critical role in bridging the charge gap. Additional potential U = 5 eV (Hubbard parameter) on top of Fe-3d potential opened a band gap of roughly 0.4 eV at the Fermi level (E F ). According to the calculations, the investigated compounds show a Mott insulator gap. The anti-ferrimagnetic states, the magnetic saturation and the computed Fe and Co moments for the ground state are in agreement with the previously reported experimental results [1]. For both experimental and theoretical results, there is a completely compression-induced change in the K-space location of the valence-band maxima.